Establishment Network by Using FSO Link Based on MD Code for Hybrid SCM-SAC-OCDMA Wireless System - Rashid Ali Fayadh; Mousa K. Wali; Mehdi F. Bonneya (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Since the wireless systems are working under nature environments and influenced by turbulence, weather in Iraq that leads to extended amount of fading signal, dissipation or attenuation. Basic “hybrid Subcarrier Multiplying Spectral Amplitude Coding (SCM-SAC) of Optical Code Division Multiple Access (OCDMA)" indoor or outdoor optical system depends on generally “Multi-Diagonal (MD)" security code by using optical space known as “Free Space Optic (FSO)" that was proposed in this work. It is found that the mention hybrid wireless systems can be used in operating mesh networks. The main proposed idea of hybrid optical technique was analyzed and simulated by normally taking into simulation account that the directly effecting by rain and haze attenuations. In addition, there are mention and description for atmospheric effects, FSO mesh network, modulation scheme, simulation, and the data security. From simulation results, the hybrid system using MD code produces reduced “bit-error rate (BER)" at heavy storm rain to distance or range of 500 m and at drizzle rain up to 2500 m range. And also investigates the performance of using the proposed system with radio over fiber (RoF) for UWB signals through indoor propagation in building applications of wireless channel.